A dense mapping study of six European AITD susceptibility regions in a large Chinese Han Cohort of Graves' disease. (1st October 2018) - Liu, Wei; Zhang, Qian‐Yue; Yuan, Fei‐Fei; Wang, Hai‐Ning; Zhang, Le‐Le; Ma, Yu‐Ru; Ye, Xiao‐Ping; Zhang, Man‐Man; Song, Zhi‐Yi; Li, Sheng‐Xian; Du, Wen‐Hua; Liang, Jun; et al.
Summary: Objective: We aimed to investigate the six susceptibility loci of GD identified from European population in Chinese Han population and further to estimate the genetic heterogeneity of them in stratification of our GD patients. Design: Dense mapping studies based on GWAS. Patients: A total of 1536 GD patients and 1516 controls in GWAS stage and 1994 GD patients and 2085 controls and 5033 GD patients and 5389 controls in two replication stages. Measurements: Based on our previous GWAS data, independently GD‐associated SNPs in each region were identified by TagSNP analysis and logistic regression analysis. The association of these SNPs was investigated in 1994 GD patients and 2085 controls, and then, the significantly associated SNPs ( P  < 0.05) were further genotyped in a second cohort including 5033 GD patients and 5389 controls. Results: After the first replication stage, four SNPs from three regions with P first  < 0.05 were further selected and genotyped in another independent cohort. The association of two SNPs with GD was confirmed in combined Chinese cohorts: rs12575636 at 11q21 ( P combined  = 7.55 × 10 −11, OR = 1.27) and rs1881145 in TRIB2 at 2p25.1 ( P combined  = 5.59 × 10 −8, OR = 1.14). Further study disclosed no significant difference for these SNPs between GD subsets. However, eQTL data revealed that SESN3 could be a potential susceptibility gene of GD in 11q21 region. Conclusions: Out of the six susceptibility loci of GD identified from European population, two risk loci were confirmed in a large Chinese Han population. There is variability in GD genetic susceptibility in different ethnic groups. SESN3 is a potential susceptible gene of GD in 11q21 .